MODELING OF A TWO ECHELON DISTRIBUTION SYSTEM OF E-COMMERCE PARCEL IN URBAN AREAS WITH PARCEL MOBILE HUB - Prastyantoro, Riharsono
E-commerce transactions are estimated to grow by 31.2%, resulting in a transaction value of around IDR 526 trillion in 2022. This transaction has increased during the pandemic because people living in urban areas have switched to buying goods online rather than offline. Online buyers are known to be very demanding where they want courier operators to deliver their parcels faster at a lower price. Courier operators face a tough challenge to provide a distribution system that is able to deliver parcels faster, at an efficient cost, and consider aspects of the urban environment. A two-echelon distribution system using a parcel mobile hub (PMH) with small vehicles can increase operational cost efficiency and reduce greenhouse gas emissions. According to a predetermined schedule, PMH brings parcels to predetermined locations in each delivery zone. This study aims to establish and test an e-commerce parcel distribution system in urban areas using a mobile hub in the form of Parcel Mobile Hub (PMH). PMH moves and conducts clearing with escorts at predetermined locations. The determination of PMH locations is based on the conceptual framework for selecting PMH locations with three variables (parcel distribution, internet quota for ecommerce transactions, and online buyer centers) and two constraints (land availability and traffic flow). There are three research objectives, namely: the establishment of an innovative two-echelon distribution system organization, the development of a conceptual framework for determining the location of the PMH fleet, and the performance of a two-echelon CEP distribution system using PMH based on efficiency and sustainability criteria. Spatial analysis is used as a method to test the conceptual framework with the package distribution database from Bandung in 2020 from one of the CEP operators. As a city whose profile represents urban areas in developing countries well, Bandung was chosen as a case study. The proportion of the distance to the variable and the outermost point of each cluster is less than 10%, which proves that the three variables are correlated. This study proves that the selection of PMH locations based on this conceptual framework results in better sustainable performance compared to the existing conditions.iv The use of PMH combined with city transport can reduce operating costs by 19.7% and prevent an additional 3.4 tons of CO2 emissions per year with conventional motorbikes and 7.2 tons of CO2 emissions per year with electric motorbikes or scooters.